Optimization of supercooling, thermal conductivity, photothermal conversion, and phase change temperature of sodium acetate trihydrate for thermal energy storage applications. (1st September 2022) - Yang, Haibin; Bao, Xiaohua; Cui, Hongzhi; Lo, Tommy Y.; Chen, Xiangsheng
Abstract: The demand for space heating and domestic hot water has caused an increase in building-energy consumption. Thermal energy storage systems can effectively solve the mismatch between heat supply and demand. Phase change materials (PCMs) can be served as the thermal storage media for thermal energy storage systems. In this study, the tailor-made sodium acetate trihydrate (SAT, a kind of PCM) was developed. Multi-wall carbon nanotubes (MWCNTs) was employed as the nucleation agent of SAT, meanwhile other carbon-based materials, including carbon fiber (CF), expanded graphite (EG), and graphene nanoplates (GNPs), were synergistically used as thermal conductivity and photothermal conversion enhancers. Ammonium chloride (NH4 Cl) was innovatively adopted as a phase change temperature regulator for SAT. The results showed that the supercooling degree of SAT decreased to 0.9 °C with the presence of MWCNTs. The thermal conductivity of SAT improved by 54.9%, and the photothermal conversion efficiency increased to 89.3% after incorporating GNPs into the SAT/MWCNTs composite. Furthermore, phase change temperature of the SAT/MWCNTs composite, ranged from 57.5 °C to 45.1 °C, could be prepared by adjusting NH4 Cl contents for satisfying different application scenarios. The results indicate that the prepared SAT composites can be potentially used in different thermal energy storage systems. Graphical abstract: Image 1 Highlights: Supercooling of SAT could be mitigated by MWCNTs. Thermal conductivity of SAT was enhanced by carbon-based materials. Photothermal conversion efficiency of SAT was increased to 89.3%. Phase change temperature of SAT could be tailored from 45 °C to 58 °C.